Augmenting Sulfur Metabolism and Herbivore Defense in Arabidopsis by Bacterial Volatile Signaling - Aziz, Mina; Nadipalli, Ranjith K.; Xie, Xitao; Sun, Yan; Surowiec, Kazimierz; Zhang, Jin-Lin; Paré, Paul W. (Frontiers in Plant Science, 2016)
Sulfur is an element necessary for the life cycle of higher plants. Its assimilation and reduction into essential biomolecules are pivotal factors determining a plant’s growth and vigor as well as resistance to environmental stress. While certain soil microbes can enhance ion solubility via chelating agents or oxidation, microbial regulation of plant-sulfur assimilation has not been reported. With an increasing understanding that soil microbes can activate growth and stress tolerance in plants via chemical signaling, the question arises as to whether such beneficial bacteria also regulate sulfur assimilation. Here we report a previously unidentified mechanism by which the growth-promoting rhizobacterium Bacillus amyloliquefaciens (GB03) transcriptionally activates genes responsible for sulfur assimilation, increasing sulfur uptake and accumulation in Arabidopsis. Transcripts encoding for sulfur-rich aliphatic and indolic glucosinolates are also GB03 induced. As a result, GB03-exposed plants with elevated glucosinolates exhibit greater protection against the generalist herbivore, Spodoptera exigua (beet armyworm). In contrast, a previously-characterized glucosinolate mutant compromised in the production of both aliphatic and indolic glucosinolates is also compromised in terms of GB03-induced protection against insect herbivory. As with in vitro studies, soil-grown plants show enhanced glucosinolate accumulation and protection against beet armyworm feeding with GB03 exposure. These results demonstrate the potential of microbes to enhance plant sulfur assimilation and emphasize the sophisticated integration of microbial signaling in plant defense.